Среда социализации и профессионально-трудовая подготовка учащихся с ограниченными возможностями - Атыгаева, Ж.Б. (My University, 2013)
The article deals with a system of Correctional and Development, Educational work in boarding school, which prepares children for an independent private and social life, affords professional working essentials, and builds a motivation for profession .